Analisa Kebutuhan Air Irigasi Untuk Tanaman Padi Dan Palawija Pada Daerah Irigasi Rawa (DIR) Danda Besar Kabupaten Barito Kuala - Fitriansyah Fitriansyah; Elva Shanty Widuri; Eriza Islakul Ulmi (Media Ilmiah Teknik Sipil, 2020)
In the management of a good irrigation system will increase the production of irrigation areas because in the Operation of an Irrigation Network should always pay attention to the Availability of Water and Water Needs and how to divide the existing water regularly and evenly so that all plants grow well. To supply water to the paddy fields and will be divided to each plot through the floodgates with an open-close system with equitable distribution so that the Water Availability and Water Needs are still metatalltimes. The research location of the Danda Besar Swamp Irrigation Area (DIR) is located in Rantau Badauh District, Barito Kuala Regency. From the results of the analysis of water availability, the minimum water requirement is 37,760 lt/sec/ha in January 1 during the rice planting season. Maximum irrigation water demand is 711,558 lt/sec/ha in April 1, which is when preparing land for palawija (maize)